The mid-Pliocene (4.3–2.6 Ma) benthic stable isotope record of the Southern Ocean: ODP Sites 1092 and 704, Meteor Rise - Andersson, Carin; Warnke, Detlef A.; Channell, James E.T.; Stoner, Joseph S.; Jansen, Eystein (Palaeogeography, Palaeoclimatology, Palaeoecology, 2002)
We present mid-Pliocene (4.3–2.6 Ma) benthic stable oxygen and carbon isotope data from Ocean Drilling Program Site 1092 (ODP Leg 177) drilled in the sub-Antarctic sector of the Southern Ocean. The results are compared with the stable isotope results from nearby Site 704 (ODP Leg 114). Oxygen isotope data show that minimum values are about 0.5‰ less than those of the Holocene, which is consistent with the results from Site 704, indicating only minor deglaciation of Antarctica during the studied interval. Oxygen isotope data from both Site 1092 and Site 704 are slightly higher relative to Pacific values during several intervals which could be related to the contribution of warm, saline North Atlantic Deep Water (NADW). Comparisons of benthic carbon isotope gradients between sites located in the North Atlantic, sub-Antarctic sector of the Southern Ocean, and Pacific indicate that at times, the gradient between the Southern Ocean and the Pacific evolved differently than the Atlantic–Pacific gradient. This suggests that variations in NADW strength alone might not be responsible for the observed carbon isotope values in the Southern Ocean.
Keywords: Sørishavet; geologi; oseanografi; paleomagnetisme; paleontologi; stabile isotoper

Skipsdagboken fra hvalkokeriet "Pythia" : beriberi utbruddet i 1928 - Børresen, Dag Ingemar (Sandar historielag, 2002)
Keywords: Norge; Sørishavet; dagbøker; hvalfangst; hvalkokerier

Contracted spleen in seals, estimates of dilated organs, and diving capacity - Cabanac, A. J. (Polar Biology, 2002)
The spleens of several seals from both the Arctic and the Antarctic were isolated and weighed when contracted. Spleens of the crabeater, leopard, and Weddell seals formed 0.23%, 0.39%, and 0.86% of the seals' body weights; those of the hooded and harp seals formed 0.56% and 0.35% of the seals' body weights. In these 5 phocids, a contracted spleen relates to the seal's body weight according to the equation (in which weights are in kilograms; n=26; r2=0.65): contracted spleen=0.006 (body weight)-0.11. Further, using the criterion reported in the literature that contracted spleens of hooded seal and harp seals weigh 80% less than when dilated, the sizes of dilated spleens were estimated for the 5 phocids of the study, plus that of the southern elephant seal. Dilated spleens ranged from 1 to 4% of the seal's body weight, which is in agreement with determinations of dilated spleens reported in the literature (harbor, 0.8–3.0%; harp, 1.5%; hooded, 2.2–4.0%). The general correlation among dilated spleens and the 6 phocids' body weights is: dilated spleen=0.026 (body weight)-0.39(where weights are in kilograms; n=31; r2=0.70). The size of the spleen (either contracted or dilated) from the different species of seals in this study appeared to be correlated with the diving capacity of the phocids, as given in the literature. The phocids with greater diving capacities are the ones with the larger spleens.
Keywords: NARE 1996/97; Sørishavet; Weddellhavet; marin biologi; pinnipedier; seler

Joint marine project during NARE 200/01: dissolved oxygen and nutrient tracers in the marine Norwegian sector of the Antarctic - Fransson, Agneta; Nøst, Ole Anders; Olsson, Kristina; O'Dwyer, Jane; Drange, Helge; Børsheim, Knut Yngve; Gammelsrød, Tor; Søreide, Janne; Karlsen, Tor Ivan; Jensen, Glen (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: NARE 2000/01; Sørishavet; biogeokjemi; ekspedisjoner; marin biologi; oseanografi

Low phytoplankton biomass and ice algal blooms in the Weddell Sea during the ice-filled summer of 1997 - Hegseth, Else Nøst; Quillfeldt von, Cecilie Hellum (Antarctic Science, 2002)
The summer of 1997 was characterized by unusually large amounts of pack ice in the southeastern Weddell Sea, and less than 10% of the area that is commonly ice-free in summer was open. A modest phytoplankton bloom developed in the upper mixed layer in the northernmost area (72°S). The bloom peaked in mid-February with max chlorophyll concentrations of 1.5 μg l−1, and integrated stocks of 55–60 mg m−2. Autotrophic flagellates dominated the biomass (80–90% of the chlorophyll) at first, while diatoms increased relative to flagellates during the bloom. Nutrient deficits, however, indicated that a much larger biomass was produced than was observed. Freezing starting after mid-February probably terminated the bloom, resulting in a pelagic growth season limited in time (less than two months) and space. The sea ice had a distinct brown layer of algae, usually at 1–2 m depth, with average chlorophyll biomass of 10.3 mg m−2. The ice cover exhibited a substantial amount of ridges, with ice algae growing in cavities and other structures, but with lower biomass than in the bands. Ice algae were also found growing on the lower 2 m of the ice shelf (visible at low tide). The overall growth season in the ice lasted several months, and ice algal production may have exceeded pelagic production in the Weddell Sea during the growth season of 1997. Pennate diatoms, like Fragilariopsis curta and F. cylindrus, dominated both in ice and in open water above the pycnocline, while Phaeocystis antarctica dominated in deeper layers and in crack pools. Euphausiids, particularly young stages, were frequently observed grazing on ice algae in ridges and on all sides of the floes, (confirmed by the gut content). Ice algae would thus have served as an ample food supply for the krill in the summer of 1997.
Keywords: Sørishavet; Weddellhavet; fytoplankton; havis alger; hydrografi; krill; oseanografi

Renewal time and transport of unventilated Central Intermediate Water of the Weddell Sea derived from biogeochemical properties - Hoppema, Mario; de Baar, Hein J. W.; Fahrbach, Eberhard; Bellerby, Richard G. J. (Journal of Marine Research, 2002)
We have investigated the intermediate water mass of the central Weddell Gyre using TCO2 and oxygen data of FS Polarstern cruises in 1992, 1996 and 1998. This water mass, designated as Central Intermediate Water (CIW), is enriched in CO2 and depleted in O-2 relative to its source water due to biological degradation. CO2 enrichment and O-2 depletion were quantified by calculating the difference between the concentrations in the CIW and those in the, more southern source water, the Circumpolar Deep Water, which derives from the Antarctic Circumpolar Current. Inventories of enrichment and depletion were determined over the whole depth range of CIW, i.e. about 200800 m. The O-2 depletion inventory was greater than that of TCO2 enrichment which is in line with a biological origin of the signal. Spatial and interannual variation appeared to be small. Because subsurface remineralization in the central Weddell Gyre is largely restricted to the CIW, the export production estimate from previous work has been applied to compute the renewal time of CIW from these inventories. A renewal time of only three years was found. TCO2- and O-2-based computations were consistent, the former showing larger variation, though. From renewal time and volume of the CIW, a transport velocity (renewal rate) of 6-7 Sv was obtained. Of this, about I Sv is upwelled into the surface layer. The remaining 5-6 Sv CIW must be exported to the north, which is opposite to previous views. Results of water mass age and transport rate have thus been obtained using a method based on biogeochemical parameters. As the CIW cannot be identified by temperature and salinity, nor with transient tracers because it is hardly ventilated, this is the only way to obtain such results. As part of the CIW export, a large amount of remineralized CO2 enters the abyssal oceans where it is sequestered for long periods of time. The CIW is a principal and highly efficient player in the biological pump mechanism of the Southern Ocean.
Keywords: AABW; Sørishavet; Weddellhavet; biogeokjemi; geofysikk; havstrømmer; oseanografi; vannmasser

Annual export production in the interior Weddell Gyre estimated from a chemical mass balance of nutrients - Hoppema, Mario; de Baar, Hein J.W.; Bellerby, Richard G.J.; Fahrbach, Eberhard; Bakker, Karel (The Southern Ocean I: Climatic Changes in the Cycle of Carbon in the Southern Ocean, 2002)
Nitrate, phosphate and silicate data are presented from 1992 austral winter and 1998 austral autumn cruises with “FS Polarstern” in the Weddell Gyre. Because in the Weddell Gyre, away from the boundary current, the surface layer is eventually formed from upwelled deep water, the difference in nutrient concentrations between these layers can be used to compute net nutrient consumptions (identical with the export production). This method renders a value for the export production that is based on observed annual changes. The results are consistent for two years and two regions within the central gyre. The calculated net nitrate and phosphate consumptions were scaled to net carbon consumptions using canonical Redfield ratios, yielding 16–17μmolCkg−1yr−1. This equals 21±4gCm−2yr−1 as a robust estimate for the marginal ice zone. The net annual silicate consumption in the surface layer, which equals the export of biogenic silica, amounts to 15–18μmolkg−1yr−1. There is a tendency for higher values in the eastern Weddell Gyre. The estimated silicate consumption of about 1.8molSim−2yr−1 is relatively high compared to earlier estimations of biogenic silica export. The silicate to carbon consumption ratio of about 1 is very high, and documents the dominance of diatoms in the export of organic material. Résumé Sont présentées les distributions verticales de nitrate, de phosphate et de silicate en Mer de Weddell, pour les périodes de l’hiver austral 1992 et de l’automne austral 1998. Les eaux de surface du tourbillon à grande échelle de la Mer de Weddell (temps de résidence égal à 2.9 ans) sont formées par l’upwelling des eaux profondes. La différence de concentrations des sels nutritifs entre les couches profondes et de surface permettent de calculer la consommation annuelle, équivalente à la production exportée de l’élément nutritif considéré vers les couches profondes. Les résultats sont comparables pour les deux scénarios annuels étudiés. La production exportée de carbone pour les eaux de surface de la zone marginale de la glace, calculée à partir des consommations annuelles en nitrates et phosphates après transformation grâce aux rapports de Redfield, est estimée à 16–17μmolCkg−1yr−1 soit en moyenne 21±4gCm−2yr−1. La consommation annuelle de silicate est estimée à 1.8mol Si m−2yr−1, relativement élevée en comparaison des estimations antérieures. Le rapport molaire Si/C, voisin de 1 dans le matériel exporté, traduit la dominance des diatomées dans l’export de matières organiques.
Keywords: Sørishavet; Weddellhavet; fytoplankton; geofysikk; karbondioksid; marin biologi; oseanografi

Species richness of marine soft sediments - John, S Gray (Marine Ecology Progress Series, 2002)
Marine soft sediments comprise one of the largest and oldest habitats in the world, yet remarkably little is known about patterns of species richness. Here I present a short review of patterns of species richness and possible factors that influence such patterns. Species richness in general is remarkably high in both shallow coastal areas and the deep sea. However, there are clear differences the deep-sea has higher number of species for a given number of individuals than the coast. This can be explained by the larger amounts of primary production that reach coastal compared with deep-sea sediments, leading to higher numbers of individuals per unit area. Species density (the number of species per unit area) is also higher in the deep-sea than in coastal areas, but it is not obvious why this is so. Most studies of the broad patterns of species richness have used samples taken at small scales only. The problem with such analyses is that unless a large number of samples are taken, the true underlying pattern (or lack of it) may be wrongly interpreted. Recent studies have analysed species richness at larger scales. In general there seems to be a cline of increasing species richness from the Arctic to the tropics, but this is not the case in the southern hemisphere, where Antarctic species richness is high. However, it is not known whether high species richness in the Antarctic occurs at all spatial scales. To what extent these patterns are determined by evolutionary factors remains to be determined by the application of molecular methods. The available evidence suggests that environmental factors such as productivity, temperature, and sediment grain-size diversity play dominant roles in determining patterns of regional-scale species richness and patterns in species turnover, and it is probably the regional scale that primarily determines local species richness. KEYWORDS: Diversity · Deep sea · Coasts · Patterns · Scales
Keywords: Sørishavet; biodiversitet; marin biologi; polarområdene

Production and mortality of phytoplankton and sea-ice microalgae in the Southern ocean - Johnsen, Geir; Børsheim, Knut Yngve; Johansen, Torunn (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Bouvetøya; NARE 2000/01; Sørishavet; alger; fytoplankton; havis; marin biologi; oseanografi; sjøis; zooplankton

Typisk pingvin!: en bok fra Antarktis - Lillevik, Linda (Eide, 2002)
Keywords: Antarktis; Sørishavet; barnebøker; fugler

Distribution and food consumption of Ross seals (Ommatophoca rossii) and Leopard seals (Hydrurga leptonyx) - Nordøy, Erling S; Blix, Arnoldus Schytte (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: NARE 2000/01; Sørishavet; havis; marin biologi; seler; sjøis; zoologi

Oceanographic measurements near Fimbulisen ice shelf - O'Dwyer, Jane; Nøst, Ole Anders; Karlsen, Tor Ivan; Søreide, Janne; Jensen, Glen; Fransson, Agneta; Savinov, Vladimir (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: NARE 2000/01; Sørishavet; Weddellhavet; glasiologi; hydrografi; oseanografi

Hvalfangere i Sydishavet og Sør-Afrika, 1910-1970 - Ødegaard, Torbjørn (Kystforl., 2002)
Keywords: Nordmenn; Sørishavet; biografier; erindringer; historie; hvalfangst; pelagisk; sjømenn

Transport and transfer of organochlorines in the marine Norwegian Antarctic sector: field sampling programme during NARE 200/01 - Olsson, Kristina; Poltermann, Michael; Savinov, Vladimir; Vögele, Barbara; Kassobokova, Ksenia; Fransson, Agneta (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: NARE 2000/01; Sørishavet; marin biologi; oseanografi; plankton

Contribution of algal sinking and zooplankton grazing to downward flux in the Lazarev Sea (Southern Ocean) during the onset of phytoplankton bloom: a lagrangian study - Pakhomov, Evgeny A.; Froneman, Pierre W.; Wassmann, Paul; Ratkova, Tatjana; Arashkevich, Elena (Marine Ecology Progress Series, 2002)
ABSTRACT: Hydrography, chlorophyll a, phytoplankton and zooplankton dynamics and the vertical flux of particulate organic carbon (POC) and pigments in the upper 200 m were investigated for 12 consecutive days during a drogue study conducted in the open waters of the ice-edge zone of the Lazarev Sea during the austral summer (December/January) 1994/95. Results of the study indicate that during the experiment, primary production, although variable, increased from ~300 to ~800 mgC m-2d-1. This increase could likely be related to development of a shallow pycnocline. Analysis of sediment trap data showed that the vertical carbon flux resulting from sedimentation and grazing activity was greatest in the upper water column (<80 m). The importance of grazers to total POC flux was highest at the beginning and the end of the investigation and accounted for up to 15% of total carbon flux. The contribution of grazers to vertical flux was negligible (<2%) during the intermediate part of the Southern Ocean Drogue study. Lower contribution of grazers to sedimentation of POC at depth can likely be related to community composition of zooplankton. Sedimentation of phytoplankton cells from the upper water column increased during the study. Here, downward POC flux resulting from sedimentation of microphytoplankton was equivalent to 15-75% of the total. Increase in sedimentation of phytoplankton during the study can be related to an increase in the average size of phytoplankton cells. Transport of POC from surface waters to deeper depths resulting from sedimentation or grazing activity was equivalent to <48% of total daily primary production, measured at 50 m, while the same value for phytoplankton flux did not exceed 27% of the total. Zooplankton density was insufficient to exert either a positive (via faecal pellets) or negative (via reducing suspended phytoplankton concentration) effect on particulate carbon sedimentation. This resulted in algal sink being the most important mechanism in downward POC flux during the onset of the phytoplankton bloom period in the Marginal Ice Zone, even in the presence of pelagic tunicates.
Keywords: Sørishavet; alger; biokjemi; marin biologi; oseanografi; phytoplankton; zooplankton

Seaweeds in Cold Seas: Evolution and Carbon Acquisition - Raven, John A.; Johnston, Andrew M.; Kübler, Janet E.; Korb, Rebecca; Mcinroy, Shona G.; Handley, Linda L.; Scrimgeour, Charlie M.; Walker, Diana I.; Beardall, John; Clayton, Margaret M.; Vanderklift, Mathew; Fredriksen, Stein; et al. (Annals of Botany, 2002)
Much evidence suggests that life originated in hydrothermal habitats, and for much of the time since the origin of cyanobacteria (at least 2·5 Ga ago) and of eukaryotic algae (at least 2·1 Ga ago) the average sea surface and land surface temperatures were higher than they are today. However, there have been at least four significant glacial episodes prior to the Pleistocene glaciations. Two of these (approx. 2·1 and 0·7 Ga ago) may have involved a ‘Snowball Earth’ with a very great impact on the algae (sensu lato) of the time (cyanobacteria, Chlorophyta and Rhodophyta) and especially those that were adapted to warm habitats. By contrast, it is possible that heterokont, dinophyte and haptophyte phototrophs only evolved after the Carboniferous–Permian ice age (approx. 250 Ma ago) and so did not encounter low (≤5 °C) sea surface temperatures until the Antarctic cooled some 15 Ma ago. Despite this, many of the dominant macroalgae in cooler seas today are (heterokont) brown algae, and many laminarians cannot reproduce at temperatures above 18–25 °C. By contrast to plants in the aerial environment, photosynthetic structures in water are at essentially the same temperature as the fluid medium. The impact of low temperatures on photosynthesis by marine macrophytes is predicted to favour diffusive CO2 entry rather than a CO2‐concentrating mechanism. Some evidence favours this suggestion, but more data are needed.
Keywords: Sørishavet; alger; biogeografi; botanikk; makroalger; marin biologi